Statins use and the risk of all and subtype hematological malignancies: a meta‐analysis of observational studies. (21st March 2015) - Pradelli, Danitza; Soranna, Davide; Zambon, Antonella; Catapano, Alberico; Mancia, Giuseppe; La Vecchia, Carlo; Corrao, Giovanni
<x xml:space="preserve">Abstract</x> In order to quantify the association between use of statins and the risk of all hematological malignancies and of subtypes, we performed a meta‐analysis of observational studies. Our study provides evidence that statins seem to reduce the risk of hematological malignancy. We also found that statins users had a significant reduced risk of leukemia and non‐Hodgkin lymphoma than nonusers.